THE ROLE OF SECURITY IN THE ORGANIZATION AND MANAGEMENT OF PUBLIC EVENTS - Xalimova Fayoza Nafasovna, (European Journal of Life Safety and Stability (2660-9630), 2021)
In the context of the transition of the economy to the principles of modern innovative management in the field of tourism, it is important to organize and diversify the quality of business meetings. Increasing the flow of tourists in the regions and creating comfortable and safe conditions for them is an urgent task today.